Bipolar membrane as well as preparation method, activation method and application thereof

By forming an adhesive layer between the cation exchange layer and the anion exchange layer of the bipolar membrane, the problem of short service life of the bipolar membrane in a high electric field and strong acid-base environment is solved, and a longer service life and better long-term operation performance are achieved.

CN119896972AActive Publication Date: 2025-04-29WANHUA CHEM GRP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311413388.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

When bipolar membranes are used in high electric field and strong acid and alkali environments, bubbles between the Yin and Yang film layers are prone to occur, resulting in a significant reduction in the durability and life of the film.

Method used

An adhesive layer is formed between the cation exchange layer and the catalyst layer, and between the anion exchange layer and the catalyst layer, preferably an adhesive layer is formed at least between the anion exchange layer and the catalyst layer. At the same time, aqueous adhesives, such as polyurethane adhesives, are used as the material for the adhesive layer.

Benefits of technology

By forming an adhesive layer, the service life of the bipolar film is significantly improved, the probability of film peeling and bubbles appearing is reduced, the long-term operation performance of the bipolar film is extended, and the voltage drop and attenuation resistance are taken into account on both sides of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896972A_ABST
    Figure CN119896972A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of bipolar membrane electrodialysis, and provides a bipolar membrane as well as a preparation method, an activation method and application thereof, the service life of the bipolar membrane provided by the invention is obviously prolonged, and the phenomena of bubbles and layering are not easy to occur in a long-time operation process. The preparation method comprises the following steps: forming an adhesive layer between the cation exchange layer and the catalyst layer, and / or forming an adhesive layer between the anion exchange layer and the catalyst layer. Preferably, the cation exchange layer is provided with a sulfonic acid group, and the anion exchange layer is provided with a quaternary ammonium group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bipolar membrane electrodialysis, and in particular to a bipolar membrane and a preparation method, an activation method and application thereof. Background Art

[0002] Bipolar membrane is an ion exchange membrane with special functions. It is usually composed of three parts: a cation exchange layer, an intermediate catalyst layer, and an anion exchange membrane layer. Under the action of the electric field, the catalyst layer in the middle of the bipolar membrane can dissociate water molecules into hydrogen ions and hydroxide ions, and then continuously transmit them to both ends of the membrane. In this process, no gas is produced. Therefore, by alternating the bipolar membrane and the anion and cation exchange membranes to form a bipolar membrane electrodialysis membrane stack system, salt can be converted into acid and alkali. Therefore, bipolar membrane electrodialysis plays an increasingly important role in the fields of lithium extraction from salt lakes, waste salt treatment, and recovery of organic acids and alkalis.

[0003] The biggest problem with bipolar membranes when used in high electric fields and strong acid-base environments is the service life of the bipolar membranes. Currently, the average service life of bipolar membranes generally does not exceed one year, and can be as short as 3-6 months. In the prior art, bipolar membranes are mostly bonded together by electrostatic attraction or hot pressing to form two layers of anion and cation exchange membranes with opposite charges. During the application process, especially when the bipolar membrane is placed under the action of strong electrolytes and strong electric fields, bubbling between the anion and cation exchange membrane layers is prone to occur, which in turn leads to peeling and shedding between the anion and cation exchange membrane layers, thereby greatly reducing the durability and life of the membrane.

[0004] The scientific journal Electrochimica Acta, Vol. 31, pp. 1175-1176, reported that the three-layer composite bipolar membrane prepared using common inorganic metal catalysts such as ruthenium trichloride is prone to ion leakage and cation and cation membrane peeling, resulting in a significant reduction in the service life of the bipolar membrane. Chinese patent publication number CN104593819A discloses a method for preparing a three-layer composite bipolar membrane using polyethylene glycol and transition metal as catalysts, which can inhibit catalyst leakage to a certain extent through coordination. Summary of the invention

[0005] The invention provides a bipolar membrane and a preparation method, an activation method and application thereof. The bipolar membrane provided by the invention has a significantly improved service life and is not prone to bubbles and stratification during long-term operation.

[0006] To achieve the purpose, the present invention provides the following technical solutions:

[0007] On one hand, the present invention provides a method for preparing a bipolar membrane, wherein the bipolar membrane comprises a cation exchange layer, an anion exchange layer, and a catalyst layer located between the cation exchange layer and the anion exchange layer, wherein the preparation method comprises the following steps: forming an adhesive layer between the cation exchange layer and the catalyst layer, and / or forming an adhesive layer between the anion exchange layer and the catalyst layer; preferably, the adhesive layer is formed at least between the anion exchange layer and the catalyst layer;

[0008] Preferably, the cation exchange layer carries sulfonic acid groups, and the anion exchange layer carries quaternary ammonium groups.

[0009] Another aspect of the present invention provides a bipolar membrane, the bipolar membrane comprising a cation exchange layer, an anion exchange layer, and a catalyst layer located between the cation exchange layer and the anion exchange layer;

[0010] An adhesive layer is provided between the cation exchange layer and the catalyst layer, and / or an adhesive layer is provided between the anion exchange layer and the catalyst layer;

[0011] Preferably, the cation exchange layer carries sulfonic acid groups, and the anion exchange layer carries quaternary ammonium groups.

[0012] Another aspect of the present invention provides a bipolar membrane prepared by the preparation method described above or a method for activating the bipolar membrane described above, wherein the bipolar membrane is activated under the action of an electric field and then washed with water;

[0013] Preferably, during the activation, the current density is 400-1000A / m 2 , the activation time is preferably 1-3h; the electric field is, for example, a direct current electric field;

[0014] Preferably, during the activation, the bipolar membrane is placed in an aqueous acetate solution, the concentration of the aqueous acetate solution is preferably 1-10 wt %, and the acetate is preferably sodium acetate and / or potassium acetate.

[0015] In another aspect, the present invention further provides an application, wherein the bipolar membrane prepared by the preparation method described above or the bipolar membrane described above is used in a bipolar membrane electrodialysis membrane device, or in the field of lithium extraction from salt lakes, waste salt treatment or recovery of organic acids and alkalis;

[0016] Preferably, the bipolar membrane is activated by the activation method described above before use.

[0017] The technical solution provided by the present invention has the following beneficial effects:

[0018] The bipolar membrane preparation method provided by the present invention has a simple process, and the prepared bipolar membrane has a longer service life, and bubbles and stratification are not easy to occur during long-term operation. At the same time, the bipolar membrane is activated under the action of an electric field before use, and has further improved application performance, and can take into account better voltage drop on both sides of the membrane, attenuation resistance and service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Shown is a schematic structural diagram of a bipolar membrane in one embodiment. DETAILED DESCRIPTION

[0020] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.

[0022] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0023] In this specification, the terms “first”, “second”, etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance.

[0024] In one aspect, the present invention provides a method for preparing a bipolar membrane, wherein the bipolar membrane comprises a cation exchange layer, an anion exchange layer, and a catalyst layer located between the cation exchange layer and the anion exchange layer, wherein the preparation method comprises the following steps: forming an adhesive layer between the cation exchange layer and the catalyst layer, and / or forming an adhesive layer between the anion exchange layer and the catalyst layer. Preferably, the cation exchange layer has a sulfonic acid group, and the anion exchange layer has a quaternary ammonium group.

[0025] The present invention forms an adhesive layer between the cation exchange layer and the catalyst layer, and / or forms an adhesive layer between the anion exchange layer and the catalyst layer. Compared with a bipolar membrane without an adhesive layer, the bipolar membrane provided in this way has a significantly improved service life, is less likely to have membrane peeling, and is less likely to have bubbles in the bipolar membrane interlayer, which can significantly improve the performance attenuation of the bipolar membrane during long-term operation.

[0026] More preferably, an adhesive layer is preferably formed at least between the anion exchange layer and the catalyst layer, which is beneficial to obtaining better bipolar membrane performance.

[0027] Furthermore, the adhesive layer is formed by applying an adhesive liquid at a position where the adhesive layer needs to be formed and then drying it. Specifically, for example, when an adhesive layer needs to be formed between a cation exchange layer and a catalyst layer, an adhesive liquid is applied to the bonding area between the cation exchange layer and the catalyst layer during the preparation of the bipolar membrane to form an adhesive layer. The formation of the adhesive layer at other positions is similar and will not be described in detail. Preferably, the concentration of the adhesive liquid is 0.5wt%-20wt%, for example, 0.5wt%, 1wt%, 3wt%, 10wt%, 15wt%, 20wt%, etc. Specifically, for example, the adhesive is pre-prepared with water into an emulsion within this concentration range.

[0028] Preferably, the adhesive is a water-based adhesive, preferably selected from one or more of polyurethane adhesive, isocyanate adhesive, acrylate adhesive and styrene-butadiene latex; the inventors found that the preferred adhesive can form a strong hydrogen bond structure with the sulfonic acid group of the cation exchange layer and / or with the quaternary ammonium group of the anion exchange layer, which can make the anion exchange layer and the cation exchange layer more tightly and firmly bonded together, and can avoid the mutual penetration problem between the anion and cation membrane layers in the bipolar membrane to a greater extent, which is conducive to further improving the efficiency of water dissociation, and at the same time, it can also be more effective to reduce the probability of anion and cation membrane peeling under long-term harsh operating conditions, which is conducive to more effectively delaying the service life of the bipolar membrane and reducing the performance attenuation amplitude. More preferably, the adhesive is a polyurethane adhesive. The inventors found that the use of a polyurethane adhesive is conducive to obtaining a bipolar membrane with better performance, further improving the voltage drop on both sides of the membrane and the performance attenuation during long-term operation.

[0029] Further preferably, the water-based adhesive is selected from Wanhua One or more combinations of a series of water-based adhesives, preferably 1630B and / or 1336, a bipolar membrane with better performance can be obtained.

[0030] In some embodiments, the thickness of the adhesive layer is 50-1000nm, for example, 50nm, 80nm, 100nm, 200nm, 300nm, 400nm, 500nm, 700nm, 900nm, 1000nm, etc., preferably 100-500nm. The inventors have found that controlling the thickness of the adhesive layer within a preferred range is beneficial for taking into account better interface bonding strength and bipolar membrane application performance, and is beneficial for further improving the voltage drop on both sides of the bipolar membrane.

[0031] Furthermore, the catalyst layer is obtained by applying a catalyst liquid at a position where the catalyst layer needs to be formed and drying it; the catalyst in the catalyst liquid is a transition metal salt, and the transition metal salt is preferably a water-soluble compound, more preferably a water-soluble transition metal chloride; preferably, the transition metal salt forms a complex with dopamine.

[0032] The inventors have found that in the adhesive-based bipolar membrane system of the present invention, transition metal salts, especially water-soluble transition metal chlorides, react with dopamine to form a complex. On the one hand, the holes of the transition metal can form a chelating coordination effect with the lone pair electrons of the amino group and the hydroxyl group on the dopamine, which is beneficial to firmly anchor the transition metal in the dopamine structure and reduce the loss of the catalyst, especially the water-soluble catalyst; on the other hand, the cation exchange layer can produce electrostatic interactions with the amino group and the hydroxyl group on the dopamine of the catalyst layer stacked thereon. Dopamine is positively charged, and the sulfonic acid groups rich in the cation membrane layer are strongly negatively charged, so that the cation exchange layer and the catalyst layer can be firmly bonded together through strong electrostatic effects; on the other hand, the amino group and the hydroxyl group rich in dopamine can also produce strong hydrogen bonding with the polar groups on the adhesive layer stacked thereon, so that the adhesive layer and the catalyst layer are firmly bonded to the cation exchange layer / anion exchange layer. Through the combined action of dopamine and adhesives as well as cation exchange layers, the bonding strength between the membrane layers in the bipolar membrane can be further enhanced, further improving the service life and performance of the bipolar membrane.

[0033] Preferably, the preparation of the catalyst liquid comprises: contacting the catalyst with dopamine under an environment of pH 3-5 (e.g., pH=3, 3.5, 4, 4.5, 5, etc.) and reacting the catalyst, and uniformly dispersing the catalyst to obtain a suspension; preferably, the reaction is carried out in the presence of ammonium persulfate. Specifically, the catalyst liquid can be evenly applied to the surface where the catalyst layer is to be formed by ultrasonic spraying, and then dried (e.g., dried in an oven at 50-150°C for 0.5-2h) to obtain the catalyst layer. The inventors have found that under the above-mentioned weakly acidic conditions, especially in the presence of ammonium persulfate, transition metal salts, especially water-soluble transition metal chlorides, can react with dopamine to form a complex, and a tight and firm composite membrane system can be formed between structures such as the catalyst layer, adhesive layer, and cation exchange layer. Specifically, the required weakly acidic environment can be provided by adding a pH adjusting agent such as hydrochloric acid. The inventors have found that if the pH is higher than 5, it is not conducive to the polymerization of dopamine catalyzed by ammonium persulfate, and if the pH is lower than 3, the stability of the complex formed by dopamine and transition metal is not high, which is not conducive to the fixation of transition metal. Carrying out the above reaction in a weak acid environment (pH 3-5) and in the presence of ammonium persulfate is conducive to the polymerization of dopamine and further realizes the anchoring of metal ions in dopamine.

[0034] Preferably, the molar ratio of the transition metal element in the catalyst to the dopamine is 1:1-1:100, preferably 1:2-1:100, such as 1:2, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, etc.; the preferred molar ratio is conducive to taking into account better catalyst layer bonding strength and catalytic effect, and is conducive to further improving the long-term operation performance of the bipolar membrane. The preferred molar ratio is conducive to obtaining a bipolar membrane with better attenuation resistance during long-term operation. More preferably, the molar ratio is 1:2-1:20, which is conducive to obtaining a bipolar membrane with better performance.

[0035] Preferably, the ammonium persulfate is added to the reaction system in the form of an aqueous solution of ammonium persulfate having a concentration of 4-6wt%, and the dopamine is added to the reaction system in the form of an aqueous solution of dopamine having a concentration of 0.5-2wt%, and the volume ratio of the aqueous solution of ammonium persulfate to the aqueous solution of dopamine is preferably 1-3:20.

[0036] Preferably, the specific type of the transition metal salt is not particularly limited, and those skilled in the art can determine the specific type of the transition metal salt used as the catalyst according to application requirements; the transition metal element in the transition metal salt is, for example, but not limited to, one or more of Fe, Sn, Cu, Cr, Co, Ni, Pd, Pt, Ag, Au or Ru, preferably Sn or Rh.

[0037] Furthermore, the cation exchange layer is prepared by using a first membrane-building liquid, wherein the first membrane-forming material contained in the first membrane-building liquid is preferably one or more of sulfonated polyetheretherketone, sulfonated polyphenylene ether, sulfonated polysulfone, and sulfonated polyethersulfone; the first membrane-building liquid can use the concentration of conventional cation exchange membranes in the art, preferably the concentration of the first membrane-building liquid is 4-40wt%, such as 4%, 10%, 20%, 30%, 40%, etc.; the solvent in the first membrane-building liquid is preferably one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, more preferably N,N-dimethylformamide. The sulfonation degree of the first membrane-forming material is, for example, 40%-100%, and the sulfonation degree refers to the molar percentage of the sulfonic acid group in the first membrane-forming material.

[0038] Further, the anion exchange layer is prepared by a second membrane-building liquid, wherein the second membrane-forming material contained in the second membrane-building liquid is preferably one or more of quaternized brominated polyphenylene ether, quaternized polysulfone, and quaternized polyethersulfone. Preferably, the quaternization degree of the second membrane-forming material is 40-70%, and the preferred quaternization degree is conducive to avoiding excessive swelling of the membrane while maintaining a high ion conductivity. The second membrane-building liquid can adopt the concentration of conventional cation exchange membranes in the art, and preferably the concentration of the second membrane-building liquid is 4-40wt%, such as 4%, 10%, 20%, 30%, 40%, etc.; the solvent in the second membrane-building liquid is preferably one or more of N,N-dimethylformamide, N,N-dimethylacetamide, chlorobenzene and N-methylpyrrolidone, more preferably N,N-dimethylformamide. The reagent for the quaternization is, for example, trimethylamine, vinylimidazole, N,N-dimethylformamide, etc., and the quaternization agent can be dissolved in a solvent for use, such as chlorobenzene. The degree of bromination of the brominated polyphenylene ether is, for example, 30-70%, where the degree of bromination refers to the molar percentage of bromine on the methyl group in the brominated polyphenylene ether.

[0039] The first film-forming material and the second film-forming material may be corresponding commercially available products, or may be prepared by a preparation method known in the art.

[0040] Furthermore, the preparation method can be specifically carried out by the following scheme 1, scheme 2 or scheme 3;

[0041] Wherein, the scheme 1 includes the following steps S1a-S4a:

[0042] S1a, providing a cation exchange layer;

[0043] S2a, applying a catalyst solution on the surface of the cation exchange layer and drying to form the catalyst layer;

[0044] S3a, applying an adhesive liquid on the surface of the catalyst layer and drying to form an adhesive layer;

[0045] S4a, stacking the anion exchange layer on the surface of the adhesive layer.

[0046] Figure 1 Shown is a schematic diagram of the structure of a bipolar membrane obtained by using Scheme 1 in one embodiment.

[0047] The second scheme includes the following steps S1b-S4b:

[0048] S1b, providing a cation exchange layer;

[0049] S2b, applying an adhesive solution on the surface of the cation exchange layer and drying to form an adhesive layer;

[0050] S3b, applying a catalyst solution on the surface of the adhesive layer in step S2b, and drying to form the catalyst layer;

[0051] S4b, applying an adhesive liquid on the surface of the catalyst layer and drying to form an adhesive layer;

[0052] S5b, stacking the anion exchange layer on the surface of the adhesive layer in step S4b.

[0053] The scheme 3 includes the following steps S1c-S4c:

[0054] S1c, providing a cation exchange layer;

[0055] S2c, applying an adhesive solution on the surface of the cation exchange layer and drying to form an adhesive layer;

[0056] S3c, applying a catalyst solution on the surface of the adhesive layer and drying to form the catalyst layer;

[0057] S4c, stacking the anion exchange layer on the surface of the catalyst layer.

[0058] In the above-mentioned schemes 1, 2 and 3, the specific operations of providing a cation exchange layer and stacking anion exchange layers can be performed by conventional operations in the art, and there is no particular restriction on this. Specifically, the cation exchange layer can be formed, for example, by dissolving the film-forming material in a solvent to prepare a first film-forming liquid of the desired concentration, and then casting the film on an ultra-flat glass plate while the solvent evaporates, and then drying (for example, drying at 100°C for 24 hours), and then cooling to room temperature to obtain a cation exchange layer. The anion exchange layer can be formed, for example, by dissolving the film-forming material in a solvent to prepare a second film-forming liquid of the desired concentration, and applying the second film-forming liquid to the surface of the adhesive layer formed in the previous step (for example, the adhesive layer formed in step S3a of scheme 1 and the adhesive layer formed in step S4b of scheme 2) or the catalyst layer surface (for example, the catalyst layer formed in step S3c of scheme 3) on the ultra-flat glass plate by a casting method, to obtain a composite multilayer bipolar membrane structure. The relevant contents of the first film-forming liquid and the second film-forming liquid can refer to the previous description, and no further description is given for this. Preferably, the bipolar membrane is prepared by adopting the above-mentioned scheme 2.

[0059] A second aspect of the present invention provides a bipolar membrane, the bipolar membrane comprising a cation exchange layer, an anion exchange layer, and a catalyst layer located between the cation exchange layer and the anion exchange layer;

[0060] An adhesive layer is provided between the cation exchange layer and the catalyst layer, and / or an adhesive layer is provided between the anion exchange layer and the catalyst layer;

[0061] Preferably, the cation exchange layer carries sulfonic acid groups, and the anion exchange layer carries quaternary ammonium groups.

[0062] In some embodiments, the thickness of the adhesive layer is 50-1000 nm, for example, 50 nm, 80 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 700 nm, 900 nm, 1000 nm, etc., preferably 100-500 nm;

[0063] Preferably, the adhesive layer is formed by a water-based adhesive, preferably selected from one or more of polyurethane adhesive, isocyanate adhesive, acrylate adhesive and styrene-butadiene latex, more preferably polyurethane adhesive; further preferably, the water-based adhesive is selected from Wanhua One or more combinations of a series of water-based adhesives, preferably 1630B and / or 1336.

[0064] In some embodiments, the catalyst in the catalyst layer is a catalyst containing a transition metal element, preferably a transition metal salt, and the transition metal salt forms a complex with dopamine; the specific type of the transition metal salt is not particularly limited, and those skilled in the art can determine the specific type of the transition metal salt as a catalyst according to application requirements. Specifically, the transition metal element in the transition metal salt is, for example, but not limited to, one or more of Fe, Sn, Cu, Cr, Co, Ni, Pd, Pt, Ag, Au or Ru. The transition metal salt is preferably a water-soluble compound, more preferably a water-soluble transition metal chloride.

[0065] Preferably, the first membrane-forming material used in the cation exchange layer is one or more of sulfonated polyetheretherketone, sulfonated polyphenylene oxide, sulfonated polysulfone, and sulfonated polyethersulfone;

[0066] Preferably, the second membrane-forming material used in the anion exchange layer is one or more of quaternized brominated polyphenylene ether, quaternized polysulfone, and quaternized polyethersulfone, and the quaternization degree of the second membrane-forming material is preferably 40-70%;

[0067] Preferably, the bipolar membrane is prepared by the preparation method described above. Where there is no special description about the bipolar membrane, reference can be made to the corresponding description about the preparation method of the bipolar membrane described above.

[0068] In the bipolar membrane provided by the present invention, the specific thickness of the anion exchange layer, the cation exchange layer and the catalyst layer can be reasonably determined by those skilled in the art according to the application requirements of the specific product, and there is no particular limitation on this. For reference, for example, the thickness of the anion exchange layer can be 20-150 μm, the thickness of the catalyst layer can be 0.1-1000 nm, and the thickness of the cation exchange layer can be 50-150 μm. One of the keys to the bipolar membrane provided by the present invention is that an adhesive layer is provided between the catalyst layer and the anion exchange layer and / or between the catalyst layer and the cation exchange layer, and preferably, the preferred embodiment mentioned above in the present invention is used to prepare the bipolar membrane during the preparation of the bipolar membrane.

[0069] In another aspect, the present invention also provides a bipolar membrane prepared by the preparation method described above or an activation method of the bipolar membrane described above, wherein the activation method comprises: activating the bipolar membrane under the action of an electric field, and then washing it, for example, with water. The inventors have found that the bipolar membrane provided by the present invention is activated under an electric field before application and then used in subsequent applications, which is beneficial to improving the application performance of the bipolar membrane and can well balance the better voltage drop on both sides of the membrane, attenuation resistance, service life, etc.

[0070] Wherein, the electric field is, for example, a direct current electric field. Preferably, during the activation, the current density is 400-1000A / m 2 , for example 400A / m 2 , 500A / m 2 、600A / m 2 , 700A / m 2 、800A / m 2 , 900A / m 2 , 1000A / m 2 etc., the activation time is preferably 1-3h, such as 1h, 1.5h, 2h, 2.5h, 3h, etc.; preferably, when performing the activation, the bipolar membrane is placed in an acetate aqueous solution, and the concentration of the acetate aqueous solution is preferably 1-10wt%. Preferably, the acetate is sodium acetate and / or potassium acetate, more preferably sodium acetate. The inventors have found that after the bipolar membrane is activated under an electric field, especially after activation under the above-mentioned preferred acetate solution and / or current conditions, the performance of the bipolar membrane can be further improved, so that the channel inside the adhesive layer is ionized to a certain extent under the action of the electric field, which is beneficial to improving the ion permeability of the adhesive layer, and is beneficial to the membrane voltage of the bipolar membrane being within a more ideal range, and is beneficial to further improve the attenuation resistance in long-term use.

[0071] Another aspect of the present invention provides an application, wherein the bipolar membrane prepared by the preparation method described above or the bipolar membrane described above is applied in a bipolar membrane electrodialysis membrane device, or in the field of lithium extraction from salt lakes, waste salt treatment, or recovery of organic acids and alkalis. Preferably, the bipolar membrane is activated by the activation method described above before application.

[0072] The technical scheme of the present invention is further described below by the following examples, but it does not mean that the present invention is limited to the following examples. The following examples are for preparing bipolar membranes using the preparation method of scheme 1. For the preparation process of bipolar membranes of schemes 2 and 3, the operations of the corresponding steps of scheme 1 can be referred to.

[0073] The schematic diagram of the bipolar membrane prepared in the following examples is shown in Figure 1 From top to bottom, there are a cation exchange layer (i.e., cation membrane layer) 1, a catalyst layer 2, an adhesive layer 3, and an anion exchange layer (i.e., anion membrane layer) 4 stacked in sequence. The catalyst layer 2 and the adhesive layer 3 are the intermediate interface structures between the cation exchange layer 1 and the anion exchange layer 4.

[0074] The contents set forth in the present invention are described in more detail below through examples.

[0075] Ingredients:

[0076] Sulfonated polyetheretherketone: prepared according to reference (Journal of Membrane Science 229 (2004) 95-106), with a sulfonation degree of about 95%;

[0077] N,N-dimethylformamide: purchased from Aladdin, purity 99%

[0078] N-Methylpyrrolidone: purchased from Aladdin, purity 98%

[0079] Dopamine: purchased from Aladdin, purity 98%

[0080] Brominated polyphenylene ether: prepared according to reference (Energy & Environmental Science, 2012, 5(7): 7888-7892), with a bromination degree of about 55%;

[0081] Vinyl imidazole: purchased from Aladdin, purity 99%;

[0082] 1630B water-based adhesive: polyurethane adhesive, Wanhua Chemical; 1336 Water-based adhesive: polyurethane adhesive, Wanhua Chemical; 161 Water-based adhesive: isocyanate adhesive, Wanhua Chemical;

[0083] Bipolar membrane hydrolysis voltage test: The test is carried out in an electrolytic cell. The cation exchange layer of the bipolar membrane corresponds to the positive electrode side of the electrolytic cell, and the anion exchange layer of the bipolar membrane corresponds to the negative electrode side of the electrolytic cell. The electrolyte is 0.5 mol / L NaCl aqueous solution, and the current density condition is 1000 A / m 2 .

[0084] Long-cycle life verification: 11 bipolar membranes, 10 cation membranes (ASTOM CMX cation membranes) and 10 anion membranes (ASTOM AMX anion membranes) were assembled into a bipolar membrane stack in the order of bipolar membrane-cation membrane-anion membrane-bipolar membrane as the smallest unit to treat 15wt% sodium sulfate aqueous solution, and the long-cycle operation performance of the bipolar membrane was investigated.

[0085] Membrane stack performance attenuation: The initial performance of the membrane stack (specifically, current efficiency) is used as a benchmark for calculation. The specific calculation formula is: (initial performance of the membrane stack - performance of the membrane stack at a certain time) / initial performance of the membrane stack * 100%

[0086] Example 1

[0087] 1) Preparation of cation exchange layer:

[0088] The dried sulfonated polyetheretherketone was weighed on a balance, then dissolved with N,N-dimethylformamide to prepare a first membrane-building solution with a mass fraction of 10wt%, and cast onto an ultra-flat glass plate (with solvent volatilization), and then placed in a 100°C forced air oven to dry for 24 hours. After being taken out and cooled to room temperature, a cation exchange layer with a thickness of 150μm was obtained.

[0089] 2) Preparation of catalyst layer:

[0090] A certain amount of dopamine was weighed to prepare a 0.5wt% dopamine aqueous solution, and the pH was adjusted with a 0.5mol / L hydrochloric acid solution to make the pH of the whole solution 4. A 5wt% ammonium persulfate aqueous solution was added (the volume ratio of the ammonium persulfate aqueous solution to the dopamine aqueous solution was 1:20). SnCl was added to the dopamine aqueous solution in a ratio of 1:2 between the transition metal element and dopamine. 2 , and then ultrasonically disperse to obtain a catalyst liquid. The prepared catalyst liquid is evenly sprayed on the upper surface of the cation exchange layer by ultrasonic spraying, and then placed in a 50°C oven for drying for 2 hours, so that the catalyst layer can be evenly attached to the surface of the cation exchange layer, and the thickness of the catalyst layer is 100nm.

[0091] 3) Preparation of adhesive layer:

[0092] Will The 1630B water-based adhesive was prepared into a pre-coating emulsion (i.e., adhesive liquid) with a concentration of 0.5 wt% using water. The adhesive liquid was evenly applied to the upper surface of the catalyst layer formed in step 2) by brushing. The entire membrane was placed in an oven at 50°C and dried for 0.5 h to obtain a three-layer structure composed of a cation exchange layer / catalyst layer / adhesive layer, wherein the thickness of the adhesive layer was 100 nm.

[0093] 4) Preparation of anion exchange layer:

[0094] The dried brominated polyphenylene ether was weighed on a balance and dissolved in an N,N-dimethylformamide solution to prepare a 20wt% brominated polyphenylene ether solution. Trimethylamine and chlorobenzene in a mass ratio of 1:10 were mixed to obtain a mixed solution. The mixed solution was slowly added to the above brominated polyphenylene ether solution (the volume ratio of the mixed solution added to the brominated polyphenylene ether solution added was 1:2) to obtain a quaternized polyphenylene ether solution with a quaternization degree of about 55% (i.e., the second membrane-building solution). The second membrane-building solution was applied to the upper surface of the adhesive layer in the three-layer structure obtained in step 3) on an ultra-flat glass plate by a casting method, and the mixture was placed in an oven at 50°C for 2h to form an anion exchange layer (with a thickness of 100μm) on the adhesive layer to obtain a composite four-layer bipolar membrane structure.

[0095] 5) Activation of bipolar membrane:

[0096] The bipolar membrane was placed in the electrolytic cell, with the cation exchange layer of the bipolar membrane corresponding to the positive electrode side of the electrolytic cell, and the anion exchange layer of the bipolar membrane corresponding to the negative electrode side of the electrolytic cell. A 3wt% sodium acetate aqueous solution was poured in, and then a current density of 1000A / m was passed. 2 The DC power supply is maintained for 1 hour, then the bipolar membrane is taken out and rinsed with deionized water.

[0097] Comparative Example 1

[0098] The bipolar membrane was prepared by referring to Example 1, except that step 2) was not performed, that is, no catalyst layer was formed between the cation exchange layer and the adhesive layer, and the cation exchange layer and the adhesive layer were directly contacted and stacked.

[0099] Comparative Example 2

[0100] The bipolar membrane was prepared by referring to Example 1, except that step 3) was not performed, that is, no adhesive layer was formed between the catalyst layer and the anion exchange layer, and the catalyst layer and the anion exchange layer were directly contacted and stacked.

[0101] The bipolar membranes of Example 1, Comparative Example 1, and Comparative Example 2 were tested according to the aforementioned bipolar membrane hydrolysis voltage test method. Test results: The voltage drop across the membrane of the bipolar membrane prepared in Example 1 was 1.15V, while the voltage drop across the membrane of the bipolar membrane of Comparative Example 1 was 5.0V, and the voltage drop across the membrane of the bipolar membrane of Comparative Example 2 was 1.10V.

[0102] The bipolar membranes of Example 1, Comparative Example 1 and Comparative Example 2 were tested according to the aforementioned long-cycle life verification method, and the results showed that: the bipolar membrane prepared in Example 1 had no bubbles or stratification after one year of operation, and its performance was attenuated by 15% compared with the initial membrane stack; the bipolar membrane of Comparative Example 1 had no stratification after one year of operation, and its performance was attenuated by 30% compared with the initial membrane stack; while the bipolar membrane in Comparative Example 2 had bubbles in the middle layer after three months of operation, and obvious stratification occurred in the anionic and cation membrane layers after half a year of operation, and the membrane stack performance was attenuated by 60% compared with the initial membrane stack performance.

[0103] Example 2

[0104] 1) Preparation of cation exchange layer:

[0105] The dried sulfonated polyetheretherketone was weighed on a balance, then dissolved with N-methylpyrrolidone to prepare a first membrane-building solution with a mass fraction of 10wt%, and cast onto an ultra-flat glass plate (with solvent evaporation), and then placed in a 100°C forced air oven to dry for 24 hours. After being taken out and cooled to room temperature, a cation exchange layer with a thickness of 150μm was obtained.

[0106] 2) Preparation of catalyst layer:

[0107] A certain amount of dopamine was weighed to prepare a 2wt% dopamine aqueous solution, and the pH was adjusted with 0.5mol / L hydrochloric acid solution to make the overall solution pH 4, and a 5wt% ammonium persulfate aqueous solution was added (the volume ratio of the ammonium persulfate aqueous solution to the dopamine aqueous solution was 3:20). RhCl was added to the dopamine aqueous solution at a molar ratio of transition metal elements to dopamine of 1:50. 3 , and then ultrasonically disperse to obtain a catalyst liquid. The prepared catalyst liquid is evenly sprayed on the upper surface of the cation exchange layer by ultrasonic spraying, and then placed in a 100°C oven for drying for 1 hour, so that the catalyst layer can be evenly attached to the surface of the cation exchange layer, and the thickness of the catalyst layer is 250nm.

[0108] 3) Preparation of adhesive layer:

[0109] Will 1336 water-based adhesive is prepared into a pre-coating emulsion (i.e., adhesive liquid) with a concentration of 10 wt% by water, and the adhesive liquid is evenly applied to the upper surface of the catalyst layer formed in step 2) by brushing. The entire membrane is placed in an oven at 100°C and dried for 0.5 h to obtain a three-layer structure composed of a cation exchange layer / catalyst layer / adhesive layer, wherein the thickness of the adhesive layer is 500 nm.

[0110] 4) Preparation of anion exchange layer:

[0111] The dried brominated polyphenylene ether was weighed on a balance and dissolved in an N-methylpyrrolidone solution to prepare a 20 wt % brominated polyphenylene ether solution. Vinyl imidazole and chlorobenzene in a mass ratio of 1:15 were mixed to obtain a mixed solution. The mixed solution was slowly added to the above brominated polyphenylene ether solution (the volume ratio of the mixed solution added to the brominated polyphenylene ether solution added was 1:2) to obtain a quaternized polyphenylene ether solution with a quaternization degree of about 55% (i.e., the second membrane-building solution). The second membrane-building solution was applied to the upper surface of the adhesive layer in the three-layer structure obtained in step 3) on an ultra-flat glass plate by a casting method, and the mixture was placed in an oven at 50°C and dried for 2 h to form an anion exchange layer (120 μm thick) on the adhesive layer to obtain a composite four-layer bipolar membrane structure.

[0112] 5) Activation of bipolar membrane:

[0113] The activation method and process of the bipolar membrane are the same as those in Example 1.

[0114] The bipolar membrane of Example 2 was tested according to the aforementioned bipolar membrane hydrolysis voltage test method and long cycle life verification method.

[0115] Test results: The voltage drop across the membrane of the bipolar membrane prepared in Example 2 is 1.20 V. The bipolar membrane prepared in Example 2 was subjected to long-term life verification. The results showed that the bipolar membrane prepared in Example 2 had no bubbles or stratification after one year of operation, and the performance of the membrane stack was attenuated by 20% compared with the initial performance.

[0116] Example 3

[0117] 1) Preparation of cation exchange layer:

[0118] The cation exchange layer was prepared by referring to step 1) of Example 1.

[0119] 2) Preparation of catalyst layer:

[0120] A certain amount of dopamine was weighed to prepare a 0.5wt% dopamine aqueous solution, and the pH was adjusted with a 0.5mol / L hydrochloric acid solution to make the pH of the whole solution 4. A 5wt% ammonium persulfate aqueous solution was added (the volume ratio of the ammonium persulfate aqueous solution to the dopamine aqueous solution was 1:20). SnCl was added to the dopamine aqueous solution at a molar ratio of transition metal elements to dopamine of 1:80. 2 , and then ultrasonically disperse to obtain a catalyst liquid. The prepared catalyst liquid is evenly sprayed on the upper surface of the cation exchange layer by ultrasonic spraying, and then placed in an oven at 100°C for 2 hours to make the catalyst layer evenly attached to the surface of the cation exchange layer. The thickness of the catalyst layer is 400nm.

[0121] 3) Preparation of adhesive layer:

[0122] Will 161 Aqueous adhesive was prepared into a pre-coating emulsion (i.e., adhesive liquid) with a concentration of 20 wt% using water, and the adhesive liquid was evenly applied to the upper surface of the catalyst layer formed in step 2) by brushing. The entire membrane was placed in an oven at 100°C and dried for 0.5 h to obtain a three-layer structure composed of a cation exchange layer / catalyst layer / adhesive layer, wherein the thickness of the adhesive layer was 1000 nm.

[0123] 4) Preparation of anion exchange layer:

[0124] The anion exchange layer was prepared by referring to step 4) of Example 1.

[0125] 5) Activation of bipolar membrane:

[0126] The activation method and process of the bipolar membrane are the same as those in Example 1.

[0127] The bipolar membrane of Example 3 was tested according to the aforementioned bipolar membrane hydrolysis voltage test method and long cycle life verification method.

[0128] Test results: The voltage drop across the membrane of the bipolar membrane prepared in Example 3 is 1.70 V. The bipolar membrane prepared in Example 3 was subjected to long-term life verification. The results showed that the bipolar membrane prepared in Example 3 had no bubbles or stratification after one year of operation, and the performance of the membrane stack was attenuated by 20% compared with the initial performance.

[0129] Example 4

[0130] 1) Preparation of cation exchange layer:

[0131] The cation exchange layer was prepared by referring to step 1) in Example 1.

[0132] 2) Preparation of catalyst layer:

[0133] A certain amount of dopamine was weighed to prepare a 2wt% dopamine aqueous solution, and the pH was adjusted with 0.5mol / L hydrochloric acid solution to make the pH of the whole solution 5. A 5wt% ammonium persulfate aqueous solution was added (the volume ratio of the ammonium persulfate aqueous solution to the dopamine aqueous solution was 1:20). RhCl was added to the dopamine aqueous solution at a molar ratio of transition metal elements to dopamine of 1:100. 3 , and then ultrasonically disperse to obtain a catalyst liquid. The prepared catalyst liquid is evenly sprayed on the upper surface of the cation exchange layer by ultrasonic spraying, and then placed in a 100°C oven for drying for 1 hour, so that the catalyst layer can be evenly attached to the surface of the cation exchange layer, and the thickness of the catalyst layer is 350nm.

[0134] 3) Preparation of adhesive layer:

[0135] Will The 1630B water-based adhesive was prepared into a pre-coating emulsion (i.e., adhesive liquid) with a concentration of 20 wt% using water. The adhesive liquid was evenly applied to the upper surface of the catalyst layer formed in step 2) by brushing. The entire membrane was placed in an oven at 50°C and dried for 0.5 h to obtain a three-layer structure composed of a cation exchange layer / catalyst layer / adhesive layer, wherein the thickness of the adhesive layer was 1000 nm.

[0136] 4) Preparation of anion exchange layer:

[0137] The anion exchange layer was prepared by referring to step 4) of Example 1.

[0138] 5) Activation of bipolar membrane:

[0139] The activation method and process of the bipolar membrane are the same as those in Example 1.

[0140] The bipolar membrane of Example 4 was tested according to the aforementioned bipolar membrane hydrolysis voltage test method and long cycle life verification method.

[0141] Test results: The voltage drop across the membrane of the bipolar membrane prepared in Example 4 was 1.50V. The bipolar membrane prepared in Example 4 was subjected to long-term life verification. The results showed that the bipolar membrane prepared in Example 4 had no bubbles or stratification after one year of operation, and the performance was attenuated by 13% compared with the initial membrane stack.

[0142] Example 5

[0143] This example is to prepare a bipolar membrane with reference to Example 1, except that step 5) is not performed, that is, the bipolar membrane is not activated.

[0144] The bipolar membrane of Example 5 was tested according to the aforementioned bipolar membrane hydrolysis voltage test method and long cycle life verification method.

[0145] Test results: The voltage drop across the membrane of the bipolar membrane prepared in Example 5 was 8.0 V. The bipolar membrane prepared in Example 5 was subjected to long-term life verification. The results showed that the bipolar membrane prepared in Example 5 had no bubbles or stratification after one year of operation, and the performance was attenuated by 35% compared with the initial membrane stack.

[0146] Example 6

[0147] The bipolar membrane was prepared by referring to Example 1, except that: in step 3), when preparing the adhesive layer, the 1630B water-based adhesive is replaced by 161 water-based adhesive.

[0148] The bipolar membrane of Example 6 was tested according to the aforementioned bipolar membrane hydrolysis voltage test method and long cycle life verification method.

[0149] Test results: The voltage drop across the bipolar membrane prepared in Example 6 was 1.50 V. The bipolar membrane prepared in Example 6 was subjected to long-term life verification. The results showed that the bipolar membrane prepared in Example 6 had no bubbles or stratification after one year of operation, and the performance was attenuated by 18% compared with the initial membrane stack.

[0150] From the comparison of the experimental results of Example 1 and Example 6, under the condition that other conditions are basically the same, the present invention uses a polyurethane adhesive to form the adhesive layer, and the obtained bipolar membrane has better performance, can obtain a better voltage drop across the membrane and better long-cycle operation performance.

[0151] Example 7

[0152] 1) Preparation of cation exchange layer:

[0153] The cation exchange layer was prepared by referring to step 1) in Example 1.

[0154] 2) Preparation of catalyst layer:

[0155] A certain amount of dopamine was weighed to prepare a 0.5wt% dopamine aqueous solution, and the pH was adjusted with a 0.5mol / L hydrochloric acid solution to make the pH of the whole solution 4. A 5wt% ammonium persulfate aqueous solution was added (the volume ratio of the ammonium persulfate aqueous solution to the dopamine aqueous solution was 1:20). SnCl was added to the dopamine aqueous solution in a ratio of 1:1 to the molar ratio of the transition metal element to dopamine. 2 , and then ultrasonically disperse to obtain a catalyst liquid. The prepared catalyst liquid is evenly sprayed on the upper surface of the cation exchange layer by ultrasonic spraying, and then placed in a 50°C oven for drying for 2 hours, so that the catalyst layer can be evenly attached to the surface of the cation exchange layer, and the thickness of the catalyst layer is 100nm.

[0156] 3) Preparation of adhesive layer:

[0157] The adhesive layer was prepared by referring to step 3) of Example 1.

[0158] 4) Preparation of anion exchange layer:

[0159] The cation exchange layer was prepared by referring to step 4) of Example 1.

[0160] 5) Activation of bipolar membrane:

[0161] The activation method and process of the bipolar membrane are the same as those in Example 1.

[0162] The bipolar membrane of Example 7 was tested according to the aforementioned bipolar membrane hydrolysis voltage test method and long cycle life verification method.

[0163] Test results: The voltage drop across the bipolar membrane prepared in Example 7 was 1.17 V. The bipolar membrane prepared in Example 7 was subjected to long-term life verification. The results showed that the bipolar membrane prepared in Example 7 had no bubbles or stratification after one year of operation, and the performance was attenuated by 19% compared with the initial membrane stack.

[0164] Example 8

[0165] 1) Preparation of cation exchange layer:

[0166] The cation exchange layer was prepared by referring to step 1) in Example 1.

[0167] 2) Preparation of catalyst layer:

[0168] The catalyst layer was prepared by referring to step 2) in Example 1.

[0169] 3) Preparation of adhesive layer:

[0170] Will The 1630B water-based adhesive was prepared into a pre-coating emulsion (i.e., adhesive liquid) with a concentration of 20 wt% using water. The adhesive liquid was evenly applied to the upper surface of the catalyst layer formed in step 2) by brushing. The entire membrane was placed in an oven at 50°C and dried for 0.5 h to obtain a three-layer structure composed of a cation exchange layer / catalyst layer / adhesive layer, wherein the thickness of the adhesive layer was 1000 nm.

[0171] 4) Preparation of anion exchange layer:

[0172] The anion exchange layer was prepared by referring to step 4) of Example 1.

[0173] 5) Activation of bipolar membrane:

[0174] The activation method and process of the bipolar membrane are the same as those in Example 1.

[0175] The bipolar membrane of Example 8 was tested according to the aforementioned bipolar membrane hydrolysis voltage test method and long cycle life verification method.

[0176] Test results: The voltage drop across the membrane of the bipolar membrane prepared in Example 8 was 1.38V. The bipolar membrane prepared in Example 8 was subjected to long-term life verification. The results showed that the bipolar membrane prepared in Example 8 had no bubbles or stratification after one year of operation, and the performance was attenuated by 15% compared with the initial membrane stack.

[0177] From the comparison between Example 1 and Example 8, when other conditions are substantially the same, Example 1 in which the thickness of the adhesive layer is controlled within the range of 100-500 nm has better bipolar membrane performance.

[0178] Example 9

[0179] 1) Preparation of cation exchange layer:

[0180] The cation exchange layer was prepared by referring to step 1) in Example 1.

[0181] 2) Preparation of catalyst layer:

[0182] The catalyst layer was prepared by referring to step 2) in Example 1.

[0183] 3) Preparation of adhesive layer:

[0184] The adhesive layer was prepared by referring to step 3) in Example 1.

[0185] 4) Preparation of anion exchange layer:

[0186] The anion exchange layer was prepared by referring to step 4) of Example 1.

[0187] 5) Activation of bipolar membrane:

[0188] The process is carried out with reference to step 5) of Example 1, except that the sodium acetate aqueous solution in Example 1 is replaced by a 3 wt % potassium acetate aqueous solution.

[0189] The bipolar membrane of Example 9 was tested according to the aforementioned bipolar membrane hydrolysis voltage test method and long cycle life verification method.

[0190] Test results: The voltage drop across the membrane of the bipolar membrane prepared in Example 9 was 1.20 V. The bipolar membrane prepared in Example 9 was subjected to long-term life verification. The results showed that the bipolar membrane prepared in Example 9 had no bubbles or stratification after one year of operation, and the performance was attenuated by 15% compared with the initial membrane stack.

[0191] From the comparison between Example 1 and Example 9, it can be seen that the bipolar membrane in the present invention is activated in a sodium acetate aqueous solution, and the effect is better.

[0192] Table 1 Summary of experimental results

[0193]

[0194]

[0195] Note: If the data in Table 1 are inconsistent with the textual descriptions in the previous embodiments / comparative examples, the previous textual descriptions shall prevail.

[0196] From the above experimental results, it can be seen that in the embodiment, an adhesive layer is added between the catalyst layer and the cation exchange layer and / or anion exchange layer of the bipolar membrane. Compared with the comparative example 2 without an adhesive layer, the long-term operation performance of the bipolar membrane can be significantly improved, the service life can be prolonged, the performance attenuation amplitude during the long-term operation can be improved, and bubbles and stratification are not easy to occur during the long-term operation.

[0197] From the experimental comparison of Example 1, Comparative Example 1 and Comparative Example 2, in the present invention, by introducing dopamine in the catalyst layer, a synergistic effect can be produced between the catalyst layer and the adhesive layer, which can more significantly improve the performance attenuation amplitude of the bipolar membrane during long-cycle operation, while taking into account a relatively low voltage drop on both sides of the membrane.

[0198] From the comparison between Example 1 and Example 5, it can be seen that by activating the bipolar membrane of the present invention under an electric field, the performance of the bipolar membrane of the present invention can be further significantly improved, and a better voltage drop across the membrane and a performance attenuation amplitude in long-term operation can be taken into account.

[0199] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A method for preparing a bipolar membrane, wherein the bipolar membrane comprises a cation exchange layer, an anion exchange layer, and a catalyst layer located between the cation exchange layer and the anion exchange layer, characterized in that: The preparation method comprises the following steps: forming an adhesive layer between the cation exchange layer and the catalyst layer, and / or forming an adhesive layer between the anion exchange layer and the catalyst layer; preferably, the adhesive layer is formed at least between the anion exchange layer and the catalyst layer; Preferably, the cation exchange layer carries sulfonic acid groups, and the anion exchange layer carries quaternary ammonium groups.

2. The preparation method according to claim 1, characterized in that: The adhesive layer is formed by applying an adhesive liquid at a position where the adhesive layer is required to be formed and then drying the adhesive liquid; preferably, the concentration of the adhesive liquid is 0.5wt%-20wt%; Preferably, the adhesive is a water-based adhesive, preferably selected from one or more of polyurethane adhesive, isocyanate adhesive, acrylate adhesive and styrene-butadiene latex; further preferably, the water-based adhesive is selected from Wanhua One or more combinations of a series of water-based adhesives, preferably 1630B and / or 1336.

3. The preparation method according to claim 1 or 2, characterized in that: The thickness of the adhesive layer is 50-1000 nm, preferably 100-500 nm.

4. The preparation method according to any one of claims 1 to 3, characterized in that The catalyst layer is obtained by applying a catalyst liquid at a position where the catalyst layer is required to be formed and drying the catalyst; the catalyst in the catalyst liquid is a transition metal salt, and the transition metal salt is preferably a water-soluble compound, more preferably a water-soluble transition metal chloride; preferably, the transition metal salt forms a complex with dopamine; Preferably, the preparation of the catalyst liquid comprises: contacting the catalyst with dopamine at a pH of 3-5 for reaction, and uniformly dispersing to obtain a suspension; preferably, the reaction is carried out in the presence of ammonium persulfate; preferably, the molar ratio of the transition metal element in the catalyst to the dopamine is 1:1-1:100, preferably 1:2-1:100, more preferably 1:2-1:20; preferably, the ammonium persulfate is added to the reaction system in the form of an aqueous solution of ammonium persulfate with a concentration of 4-6wt%, and the dopamine is added to the reaction system in the form of an aqueous solution of dopamine with a concentration of 0.5-2wt%, and the volume ratio of the aqueous solution of ammonium persulfate to the aqueous solution of dopamine is preferably 1-3:20; Preferably, the transition metal element in the transition metal salt is one or more of Fe, Sn, Cu, Cr, Co, Ni, Pd, Pt, Ag, Au or Ru.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The cation exchange layer is prepared by using a first membrane-building liquid, wherein the first membrane-forming material contained in the first membrane-building liquid is one or more of sulfonated polyetheretherketone, sulfonated polyphenylene ether, sulfonated polysulfone, and sulfonated polyethersulfone, and the degree of sulfonation is, for example, 40-100%; preferably, the concentration of the first membrane-building liquid is 4-40wt%; the solvent in the first membrane-building liquid is preferably one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, more preferably N,N-dimethylformamide; And / or, the anion exchange layer is prepared using a second membrane-building liquid, wherein the second membrane-forming material contained in the second membrane-building liquid is one or more of quaternized brominated polyphenylene ether, quaternized polysulfone, and quaternized polyethersulfone; preferably, the quaternization degree of the second membrane-forming material is 40-70%; preferably, the concentration of the second membrane-building liquid is 4-40wt%; and the solvent in the second membrane-building liquid is preferably one or more of N,N-dimethylformamide, N,N-dimethylacetamide, chlorobenzene and N-methylpyrrolidone, more preferably N,N-dimethylformamide.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method is carried out by the following scheme 1, scheme 2 or scheme 3; Wherein, the scheme 1 includes the following steps S1a-S4a: S1a, providing a cation exchange layer; S2a, applying a catalyst solution on the surface of the cation exchange layer and drying to form the catalyst layer; S3a, applying an adhesive liquid on the surface of the catalyst layer and drying to form an adhesive layer; S4a, stacking the anion exchange layer on the surface of the adhesive layer; The second scheme includes the following steps S1b-S4b: S1b, providing a cation exchange layer; S2b, applying an adhesive solution on the surface of the cation exchange layer and drying to form an adhesive layer; S3b, applying a catalyst solution on the surface of the adhesive layer in step S2b, and drying to form the catalyst layer; S4b, applying an adhesive liquid on the surface of the catalyst layer and drying to form an adhesive layer; S5b, stacking the anion exchange layer on the surface of the adhesive layer in step S4b; The scheme 3 includes the following steps S1c-S4c: S1c, providing a cation exchange layer; S2c, applying an adhesive solution on the surface of the cation exchange layer and drying to form an adhesive layer; S3c, applying a catalyst solution on the surface of the adhesive layer and drying to form the catalyst layer; S4c, stacking the anion exchange layer on the surface of the catalyst layer.

7. A bipolar membrane, characterized in that The bipolar membrane comprises a cation exchange layer, an anion exchange layer, and a catalyst layer located between the cation exchange layer and the anion exchange layer; An adhesive layer is provided between the cation exchange layer and the catalyst layer, and / or an adhesive layer is provided between the anion exchange layer and the catalyst layer; Preferably, the cation exchange layer carries sulfonic acid groups, and the anion exchange layer carries quaternary ammonium groups.

8. The bipolar membrane according to claim 7, characterized in that The thickness of the adhesive layer is 50-1000nm, preferably 100-500nm; And / or, the adhesive layer is formed by a water-based adhesive, preferably selected from one or more of a polyurethane adhesive, an isocyanate adhesive, an acrylate adhesive and styrene-butadiene latex; further preferably, the water-based adhesive is selected from Wanhua One or more combinations of a series of water-based adhesives, preferably 1630B and / or 1336; And / or, the catalyst in the catalyst layer is a catalyst containing a transition metal element, wherein the transition metal element is, for example, one or more of Fe, Sn, Cu, Cr, Co, Ni, Pd, Pt, Ag, Au or Ru; preferably, the catalyst is a transition metal salt, and the transition metal salt forms a complex with dopamine; the transition metal salt is preferably a water-soluble compound, more preferably a water-soluble transition metal chloride; And / or, the first membrane-forming material used in the cation exchange layer is one or more of sulfonated polyetheretherketone, sulfonated polyphenylene oxide, sulfonated polysulfone, and sulfonated polyethersulfone; And / or, the second membrane-forming material used in the anion exchange layer is one or more of quaternized brominated polyphenylene ether, quaternized polysulfone, and quaternized polyethersulfone, and preferably the quaternization degree of the second membrane-forming material is 40-70%; Preferably, the bipolar membrane is prepared by the preparation method according to any one of claims 1 to 7.

9. The bipolar membrane prepared by the preparation method according to any one of claims 1 to 6 or the activation method of the bipolar membrane according to claim 7 or 8, characterized in that: activating the bipolar membrane under the action of an electric field, and then washing with water; Preferably, during the activation, the current density is 400-1000A / m 2 , the activation time is preferably 1-3h; the electric field is, for example, a direct current electric field; Preferably, during the activation, the bipolar membrane is placed in an aqueous acetate solution, the concentration of the aqueous acetate solution is preferably 1-10 wt %, and the acetate is preferably sodium acetate and / or potassium acetate.

10. An application, characterized in that: The bipolar membrane prepared by the preparation method according to any one of claims 1 to 6 or the bipolar membrane according to claim 7 or 8 is used in a bipolar membrane electrodialysis membrane device, or in the field of lithium extraction from salt lakes, waste salt treatment or recovery of organic acids and alkalis; Preferably, the bipolar membrane is activated by the activation method according to claim 9 before use.

Citation Information

Patent Citations

  • Bipolar membrane and preparation method thereof

    CN104593819A

  • A bipolar membrane and a preparing method thereof

    CN108031302A

  • Bipolar membrane with copper-metal organic framework material as intermediate interface layer and preparation method of bipolar membrane

    CN108842164A

  • Bipolar membrane using zinc-metal organic framework material as middle interface layer and preparation method thereof

    CN108866567A

  • Bipolar membrane for sepn. by electrodialysis - comprises anion- and cation-selective layers and intermediate ultra-thin layer of polyelectrolyte complex with excess acid or basic gps.

    DE4026154A1